Strategic Management Model as a Driver of Creative Industry Performance and Innovation - Muhamad Agung Dharmajaya (Sean Institute, 2025)
The creative industry plays a strategic role in driving economic growth and creating added value based on creativity and innovation. However, uncertain market dynamics, the development of digital technology, and high levels of competition require creative industry players to implement adaptive and sustainable strategic management. This study aims to analyze strategic management models as drivers of creative industry performance and innovation, and to identify challenges faced in their implementation. This study used a qualitative approach with descriptive methods, through the collection of primary and secondary data. Primary data were obtained through in-depth interviews with creative industry players, while secondary data came from government policy documents, creative industry reports, and related literature. Data analysis was conducted qualitatively through data reduction, data presentation, and conclusion drawing. The results indicate that a strategic management model encompassing the stages of performance, programming, design, implementation, and marketing plays a crucial role in integrating creative ideas into sustainable economic value. Furthermore, the implementation of Digital Business Model Innovation, Blue Ocean Strategy, ecosystem strengthening, and Intellectual Property Rights protection have been shown to support improved creative industry performance and innovation. However, this study also identified various challenges, such as limited human resource capacity, access to technology and data, weak IPR protection, and market uncertainty. This research is expected to provide theoretical contributions to the development of strategic management studies in the creative industry and serve as a practical reference for business actors and policymakers in formulating strategies for developing a competitive and sustainable creative industry.